Sunlight-driven degradation of acid red 14 using a ZnO-doped carbon-ammonia composite: kinetics, equilibrium, and thermodynamic studies - Alprol, Ahmed E.; Bakr, Ahmed; Al-Saeedi, Sameerah I.; El-Haroun, Ehab; Ashour, Mohamed (Frontiers in Marine Science, 2025)
To identify the efficacy of a ZnO-doped activated carbon-ammonia (AC-ZnO-NH3) composite on photocatalytic degradation of Acid Red 14 (AR14) dye from aqueous solutions, the compositional and structural properties of the assembled composite were evaluated by FTIR, XRD, SEM and EDX. The material was synthesized and characterized using FTIR, XRD, SEM, and EDX, confirming the successful incorporation of ZnO and nitrogen functionalities. The composite achieved a maximum AR14 removal efficiency of 95.55% under optimal conditions (pH 3, catalyst dose of 0.18 g, and dye concentration of 25 mg/L). The kinetic data fitted well with the pseudo-second-order model, suggesting chemisorption as the primary mechanism. Adsorption equilibrium followed the Henderson isotherm model, indicating a heterogeneous surface. Thermodynamic analysis revealed that the process is endothermic and spontaneous at higher temperatures, with positive ΔH° and negative ΔG° values. Additionally, the presence of hydrogen peroxide (H2O2) enhanced photocatalytic efficiency by reducing the dye’s half-life from 382.9 min to 289.3 min. The composite exhibited partial reusability across three cycles, supporting its potential for practical application. These findings highlight the composite’s effectiveness as a sustainable and cost-efficient photocatalyst for azo dye removal under natural sunlight.